FEATURES OF THE CLINICAL PICTURE IN SEVERE CHRONIC OBSTRUCTIVE PULMONARY DISEASE - M. L. Steiner; A. V. Zhestkov; E. V. Brylyaeva (Klinicist)
Objective — to study features of severe chronic obstructive pulmonary disease (COPD) aggravation.Materials and methods. We examined 1969 patients with acute severe COPD who were hospitalized in the intensive care unit with progressiverespiratory insufficiency, and depression of his own expectoration during the period from 2004 to 2011, chest radiography, electrocardiography,pulse oximetry, blood gas study, bronchoscopy were performed in all patients on admission.Results. In many patients, there was a significant deterioration in expectoration, up to complete suppression. This made it difficult to identify the two major symptoms of the classic triad of exacerbation (increased bronchial secretions and increase of pyogenesis). However, during fiberoptic scope examination massive obstruction of the lower parts was revealed on the level of tracheobronchial tree by bronchial secretion, which had purulent or muco-purulent character.Conclusion. Severe rapid increasing obstruction of the lower respiratory tract by bronchial secretion in inefficient natural expectoration should be considered as an equivalent of COPD exacerbation.